A multicenter, prospective, randomized controlled trial of intracranial hemorrhage risk of intensive statin therapy in patients with acute ischemic stroke combined with cerebral microbleeds (CHRISTMAS): Study protocol - Zhao, Jia-ling; Ai, Chi-bo; Wang, Li; Yang, Shao-jie; Wang, Jian; Yang, Wei; Tang, Jie; Zhang, Ling; Li, Yan; Yan, Ting-qi; Gou, Shu; Xie, Gui-gui; et al. (Frontiers in Neurology, 2023)
Background Low serum levels of major lipid markers have been proved to be significantly associated with increased risks of hemorrhagic stroke (HS) and cerebral microbleeds (CMBs). However, there is no lipid modification guideline telling us how to maintain a balance between the prevention of ischemic stroke recurrence and the prevention of hemorrhagic events, especially in patients with acute ischemic stroke (AIS) and CMBs. Aim The Intracranial Hemorrhage Risk of Intensive Statin Therapy in Patients with Acute Ischemic Stroke combined with Cerebral Microbleeds (CHRISTMAS) trial evaluates the risk of intracranial hemorrhage (i.e., HS and CMBs) of high-dose statin therapy in patients with AIS combined with CMBs. Methods and design This is an investigator-initiated, multicenter, prospective, randomized controlled clinical trial design. Up to 344 eligible patients will be consecutively randomized to receive high-dose or low-dose atorvastatin in 1:1 ratio in 5 stroke centers in China. Outcomes CHRISTMAS trial has co-primary outcomes, namely, hemorrhage risk: the incidence of HS and the changes in degree of CMBs until the end of 36-month follow-up. Discussion The primary hypothesis of this study is that an excessive reduction in serum lipid levels by an intensive statin therapy in AIS patients with CMBs can increase the risk of intracranial hemorrhage. This study will shed light on new clinical decisions regarding the long-term serum lipid management in these patients with dilemma in clinical practice. Clinical trial registration Clinicaltrials.gov, identifier: NCT05589454.